2013
DOI: 10.1371/journal.pone.0081015
|View full text |Cite
|
Sign up to set email alerts
|

A Rad53 Independent Function of Rad9 Becomes Crucial for Genome Maintenance in the Absence of the RecQ Helicase Sgs1

Abstract: The conserved family of RecQ DNA helicases consists of caretaker tumour suppressors, that defend genome integrity by acting on several pathways of DNA repair that maintain genome stability. In budding yeast, Sgs1 is the sole RecQ helicase and it has been implicated in checkpoint responses, replisome stability and dissolution of double Holliday junctions during homologous recombination. In this study we investigate a possible genetic interaction between SGS1 and RAD9 in the cellular response to methyl methane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
3
9
0
Order By: Relevance
“…In the absence of Rad9, cells fail to properly activate the DNA-damage checkpoint and DNA ends undergo rapid end resection (Lazzaro et al, 2008). Cells lacking RAD9 exhibit a greater incidence of non-allelic recombination, and this defect is consistent with the fact that loss of RAD9 frequently produces synergistic increases in chromosomal rearrangement in mutants lacking factors responsible for the regulation of homology-directed repair (Fasullo, Bennett, Ahching, & Koudelik, 1998; Nielsen, Bentsen, Andersen, Gasser, & Bjergbaek, 2013).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the absence of Rad9, cells fail to properly activate the DNA-damage checkpoint and DNA ends undergo rapid end resection (Lazzaro et al, 2008). Cells lacking RAD9 exhibit a greater incidence of non-allelic recombination, and this defect is consistent with the fact that loss of RAD9 frequently produces synergistic increases in chromosomal rearrangement in mutants lacking factors responsible for the regulation of homology-directed repair (Fasullo, Bennett, Ahching, & Koudelik, 1998; Nielsen, Bentsen, Andersen, Gasser, & Bjergbaek, 2013).…”
Section: Introductionsupporting
confidence: 68%
“…Mec1 signaling therefore switches to an anti-checkpoint and pro-resection mode. Once long-resection occurs, extensive ssDNA accumulates, leading to increased opportunities for strand invasion, but also increased opportunities for non-allelic recombination ( rad9Δ cells have increased non-allelic recombination, (Fasullo, Bennett, Ahching, & Koudelik, 1998; Nielsen, Bentsen, Andersen, Gasser, & Bjergbaek, 2013)). In this context, we propose that a new mode of Mec1 signaling triggered by extensive resection stabilizes the STR complex at lesions via interaction with Dpb11 for proper regulation of HR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Segurado and Diffley (Segurado & Diffley, ) have described two ways of replication fork stabilization by Rad53: an Exo1‐dependent pathway that mainly reacts to MMS, UV or ionizing radiation damage, and an Exo1‐independent mechanism that is more important after exposure to HU. Similarly, Nielsen et al () have proposed that an HU‐stalled fork adopts a structure distinct from one that is stalled by MMS, consistent with the notion that the replisome component Mrc1 dominates HU‐induced checkpoint signaling, whereas the response to MMS depends on Rad9 (Alcasabas et al , ; Crabbe et al , ; Nielsen et al , ). Yet, the stalled replication fork as the origin of the checkpoint signal in response to replication stress has not been called into question.…”
Section: Discussionmentioning
confidence: 68%
“…CHK1 may also constitutively phosphorylate BLM to prevent proteasome-dependent BLM degradation, suppress chromatin bridge formation, and promote an interaction with 53BP1 (Sengupta et al, 2004;Tripathi et al, 2007;Kaur et al, 2010;Petsalaki et al, 2014). Interestingly, in yeast, Rad53 and Sgs1 (a BLM ortholog) physically interact (Hegnauer et al, 2012), and Sgs1 has been reported to display a strong genetic interaction with Rad9, 53BP1's yeast homolog (Nielsen et al, 2013). Finally, David Cortez's group described an additional mechanism of fork stability regulation through the ATR's phosphorylation of the SMARCAL1 helicase (Couch et al, 2013).…”
Section: Of 21mentioning
confidence: 99%